The discovery of grounded theory : strategies for qualitative research - Glaser, Barney G. (Aldine Transaction, 2011)
Is directed toward improving social scientist's capacity for generating theory that will be relevant to their research. While aimed primarily at sociologists, it will be useful to anyone interested in studying social phenomena-political, educational, economic, industrial-especially if their studies are based on qualitative data.